Critical success factors of e-learning among adult learners in Open University Malaysia Johor Bahru, Malaysia - P. R. Harishen Panrangam, 1988-, author; Rozeyta Omar, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2011)
Project Paper (Sarjana Muda Sains (Pembangunan Sumber Manusia)) - Universiti Teknologi Malaysia, 2011